Differential Wnt/β-catenin signaling via TCF7L2/LEF1 binding specificity shapes cellular and tumor phenotypes - Thomas A. Kluiver; Anna Nordin; Yuyan Lu; Xuan Guo; Stephanie A. Schubert; Darien Yeung; Arif Ibrahim Ardisasmita; Wessel Terpstra; Chang Zhang; Xiaochen Duan; Rishi Savur; Marius C. van den Heuvel; et al. (Proceedings of the National Academy of Sciences, 2026)
The mechanisms by which Wnt/β-catenin signaling regulates gene expression in a tissue- and context-specific manner remain poorly understood, limiting our ability to target the aberrant cell growth typical of many Wnt-driven cancers. Here, we focus on malignant liver tumors driven by activating CTNNB1 (β-catenin) mutations that nevertheless display distinct phenotypic states and Wnt outputs. By profiling patient-derived organoids via single-cell transcriptomics and chromatin dynamics, we identify subtype-specific transcriptional and epigenetic profiles. Using CUT&RUN, we show that β-catenin engages distinct genomic regions, dictated by differential association with TCF/LEF family transcription factors. Specifically, we define a sequence-specific regulatory element engaged by β-catenin only upon interaction with TCF7L2, revealing that partner choice, independent of CTNNB1 mutational status, ultimately determines cell fate. Our findings, validated across multiple tumor models and patient tissues, offer a framework for understanding how differential β-catenin-TCF/LEF interaction orchestrates context-specific Wnt signaling outcomes.